Nanodiamond 2014
DOI: 10.1039/9781849737616-00221
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Nucleation and Seeding Techniques: Two Complementary Strategies for the Growth of Ultra-thin Diamond Films

Abstract: The controlled growth of ultra-thin diamond layers on a diversity of substrates is a major challenge for many technological applications (heat spreaders, electromechanical systems, etc.). This explains the huge effort produced during the last two decades to master the early stages of diamond formation. Two main pathways have been investigated in the literature. The nucleation pathway aims to produce diamond nuclei, i.e., the smallest thermodynamically stable diamond islands, at the substrate surface. This is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 161 publications
0
11
0
Order By: Relevance
“…Indeed, seeding with NDs represents an alternative to in situ nucleation methods like Bias Enhanced Nucleation (BEN) [20]. Sequential XPS analysis confirmed the stability of detonation NDs (5 nm) under CVD conditions [94].…”
Section: Deposition Of Ndsmentioning
confidence: 76%
See 2 more Smart Citations
“…Indeed, seeding with NDs represents an alternative to in situ nucleation methods like Bias Enhanced Nucleation (BEN) [20]. Sequential XPS analysis confirmed the stability of detonation NDs (5 nm) under CVD conditions [94].…”
Section: Deposition Of Ndsmentioning
confidence: 76%
“…Contrary to BEN, 3D substrates like silicon tips [102,103] or silica optical fibers [104] can be homogeneously coated [105]. The main challenge is the improvement of diamond films adhesion [20,93]. An optimized seeding would combine a high density of seeds (up to 10 11 /cm 2 ) with a seed size as small as possible.…”
Section: Deposition Of Ndsmentioning
confidence: 97%
See 1 more Smart Citation
“…Before synthesizing the ND films by CVD, a diamond seeding process is a critical step to essentially enhance the nucleation quality and smoothness of ND film in non-carbide forming substrates [ 42 , 43 , 44 ]. Many seeding procedures are employed for the ND film growth, including mechanical abrasion method with a diamond grit, spin-off coating method on the substrate with a diamond-containing particles, printing method of seeds by a stamp brought in contact with the substrate, ultrasonic treatment method in a suspension of diamond powder, and bias-enhanced nucleation (BEN) deposition of diamond on a substrate [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The quality of ND film is directly dependent on the seeding parameter, such as the density and size distribution of ND particles.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Stable fluorescence properties could be also introduced through nitrogen vacancy centers created by irradiation and annealing. A large number of in vitro and in vivo studies have confirmed that ND have very low cytotoxicity on numerous cell lines including osteoblasts and neuroblasts, glial and marrow, liver, kidney, intestine and lung cells. Further than simple biocompatibility due to chemical inertness, Thalhammer et al reported that an ND monolayer coating even promotes the formation of a functional neuronal network. , Finally, diamond nanoparticles exhibit excellent tribological properties. , All the properties mentioned above make ND highly desirable for a wide range of applications in various fields, either dispersed in colloids or deposited on a surface. The latter case includes seeding prior to film growth by chemical vapor deposition (CVD), protective coatings against corrosion, , tissue scaffold engineering, , platforms for protein immobilization on biosensors, sensitive coatings for surface acoustic wave sensors and attachment to probe for nitrogen-vacancy center mapping …”
Section: Introductionmentioning
confidence: 99%